Microbial respiration per unit biomass increases with carbon-to-nutrient ratios in forest soils. (February 2015) - Spohn, Marie; Chodak, Marcin
Abstract: The ratio of carbon-to-nutrient in forest floors is usually much higher than the ratio of carbon-to-nutrient that soil microorganisms require for their nutrition. In order to understand how this mismatch affects carbon (C) cycling, we investigated the respiration rate per unit soil microbial biomass – the metabolic quotient (qCO2 ) – in relation to the soil carbon-to-nitrogen (C:N) and carbon-to-phosphorus (C:P) ratio in temperate forests. For this purpose, cores of beech, spruce, and mixed spruce-beech forest soils were cut into slices of 1 cm from the litter layer down to 5 cm in the mineral soil, and the relationship between the qCO2 and the soil C:N and the soil C:P ratio was analyzed. We found that the qCO2 was positively correlated with soil C:N ratio in spruce soils ( R = 0.72), and with the soil C:P ratio in beech ( R = 0.93), spruce ( R = 0.80) and mixed forest soils ( R = 0.96). We also observed a close correlation between the qCO2 and the soil C concentration in all three forest types. Yet, the qCO2 decreased less with depth than the C concentration in all three forest types, suggesting that the change in qCO2 is not only controlled by the soil C concentration. We conclude that microorganisms increase their respiration rate per unit biomass with increasing soil C:P ratio and C concentration, which adjusts the substrate to their nutritional demands in terms of stoichiometry. Highlights: The qCO2 (respiration rate per unit microbial biomass) increased with soil C:N ratio in spruce soils. The qCO2 increased with soil C:P ratio in beech, spruce, and mixed forest soils. Microorganisms adjust the substrate to their nutritional demands in terms of C:N:P stoichiometry.